Chemoselective RuII‐Catalyzed Synthesis of Aryl Thiocyanates and Step‐wise Double [2+2+2] Cycloadditions to 2‐Aryl Thiopyridines. Issue 29 (22nd June 2020) - Bhatt, Divya; Kalaramna, Pratibha; Kumar, Krishn; Goswami, Avijit
Abstract : Ru II ‐catalyzed intermolecular double [2+2+2] cycloadditions of 1, 6‐diynes and alkynylthiocyanates have been developed for the synthesis of 2‐aryl thiopyridines. Aryl thiocyanates were isolated chemoselectively as a result of initial intermolecular [2+2+2] cycloaddition product. The method offers operational simplicity and is atom economical in nature. Abstract : An atom‐economical approach towards the synthesis of aryl thiocyanates has been documented employing ruthenium‐catalyzed [2+2+2] cycloaddition strategy. Sequential Ru II ‐catalyzed intermolecular [2+2+2] cycloadditions of 1, 6‐diynes and formed aryl thiocyanates resulted in the synthesis of 2‐aryl thiopyridines.